Mapping for connection, a life beyond mapping for control: lessons from ‘mapping-as-performance’ with Empatheatre in South Africa - Whittingham, Jennifer; McGarry, Dylan (Frontiers in Marine Science, 2024)
This paper critically examines the intersections of Science, colonialism, and cartography in shaping perceptions of the ocean and its human-nature relationships. Drawing on Postcolonial Science and Technology Studies (PCSTS) and Decolonial Theory, it scrutinizes historical mapping practices, revealing how they perpetuated ontological hierarchies and controlled narratives of the ocean. Through archival research spanning from the Revolution to colonial exploration, the paper exposes how maps framed the ocean as a controllable entity, obscuring socio-cultural dimensions of biodiversity. Focusing on a case study in Northern Kwazulu-Natal, South Africa, the authors explore an Empatheatre mapping process, that challenges Western ontologies and promotes counter-hegemonic cartographic practices. Situating this within critical cartography and PCSTS literature, the paper reveals how colonial projects molded perceptions of oceanic space and influenced environmental governance. In the South African context, the ocean is haunted by a violent history of racial exclusion and ecological exploitation. Initiatives like Operation Phakisa’s Blue Economy plan underscore the tension between economic growth and ecological sustainability, leading to rapid coastal developments. Marine Spatial Planning (MSP) emerges as a tool to reconcile these interests, yet its implementation raises questions about inclusivity and community participation. Introducing the Empatheatre method, characterized by a ‘Call and Response’ approach, the paper invites local communities to co-create maps reflecting their concerns and relationships with the ocean. Through attentive listening and collaborative storytelling, Empatheatre challenges traditional consultation methods, prioritizing meaningful engagement and collective meaning-making. Mapping in this context is not merely a static representation but a dynamic process of collective thinking and relationality. By foregrounding the social, cultural, and ecological context, Empatheatre’s approach redefines the mapmaker-map relationship and empowers communities as active agents in shaping their narratives. The transformative potential of Empatheatre lies in its ability to shift power dynamics and foster empathy between diverse stakeholders. Through performative storytelling and visual representations, Empatheatre creates space for marginalized voices and alternative modes of knowledge transmission. In conclusion, this paper advocates for a decolonial approach to oceanic cartographies that acknowledges diverse ontologies and fosters inclusive governance structures.